Lifetime use of nonsteroidal anti-inflammatory drugs and breast cancer risk: results from a prospective study of women with a sister with breast cancer. Issue 1 (December 2015) - Kim, Sangmi; Shore, David; Wilson, Lauren; Sanniez, Ethel; Kim, Jae; Taylor, Jack; Sandler, Dale
Abstract Background Nonsteroidal anti-inflammatory drugs (NSAIDs) have been shown to inhibit several pathways in experimental models of breast carcinogenesis, but epidemiological evidence remains insufficient to support their use for breast cancer prevention. We examined the association between use of NSAIDs and breast cancer risk in a prospective cohort. Methods The Sister Study is a prospective cohort study of women who had a sister(s) with breast cancer. As of December 2013, 2118 incident breast cancers were ascertained from 50, 884 women enrolled between 2003 and 2009. Lifetime history of NSAID use was estimated from self-reported data in pill-years, with 1 pill per week for a year equivalent to 1 pill-year. Cox regression models were used to estimate hazard ratios (HRs) of breast cancer in relation to pill-years of use for different NSAIDs, with adjustment for potential confounders. Results In the full cohort, although there was some evidence that use of non-aspirin, non-COXib NSAIDs was associated with lower breast cancer risk, there was little evidence of overall association for most categories of NSAID use. Among postmenopausal women NSAID use was not associated with reduced risk of breast cancer. However, among premenopausal women there was significantly reduced risk for any NSAID (HR4vs1  = 0.66, 95 % CI: 0.50–0.87) and specifically for aspirin (HR4vs1  = 0.57, 95 % CI: 0.33–0.98), with small, but non-significant reductions in risk for other drug classes. Conclusion Women with a sister with breast cancer are themselves at increased risk and might benefit the most from chemoprevention. Although there was little evidence of protective effect from NSAIDs in the overall cohort of women or among the subset who are postmenopausal, there is intriguing evidence that NSAID use, particularly aspirin, may reduce risk among premenopausal women.